1999
DOI: 10.1111/j.1095-8649.1999.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of the duration of the egg collecting phase in the three‐spined stickleback

Abstract: Individual male three-spined sticklebacks in the field, often collected eggs for longer (up to 10 days) than had been reported for sticklebacks in captivity (3-6 days). The probability that a male stopped collecting eggs increased with the number of eggs already present, and possibly with the age of the eggs. Males with nests hidden under a plant were more likely to continue collecting than males with exposed nests. These results are discussed in the light of theoretical considerations that predict when males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…One has to realize, however, that males guarded only one clutch in the experiment, which is on the low end of the natural range. In the wild, males often collect several clutches from different females, thus a nest might contain more than thousand eggs (Kynard 1978;Kraak et al 1999a;Bakker et al 2006b). In teleost fishes, small broods face a higher risk of being cannibalized (Ochi 1985;Schwank 1986;Forsgren et al 1996;Okuda & Yanagisawa 1996;Lindströ m & Sargent 1997;Lissåker & Svensson 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One has to realize, however, that males guarded only one clutch in the experiment, which is on the low end of the natural range. In the wild, males often collect several clutches from different females, thus a nest might contain more than thousand eggs (Kynard 1978;Kraak et al 1999a;Bakker et al 2006b). In teleost fishes, small broods face a higher risk of being cannibalized (Ochi 1985;Schwank 1986;Forsgren et al 1996;Okuda & Yanagisawa 1996;Lindströ m & Sargent 1997;Lissåker & Svensson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To be able to distinguish the eggs of different females, either foreign or own eggs, in alternated order between experiments, were dyed slightly blue by placing them in a solution of Alcian blue (2 g 100 ml 21 ) for 30 min (Kraak et al 1997). In several previous studies, this method did not influence egg survival or cannibalistic behaviour (Kraak et al 1997(Kraak et al , 1999aFrommen et al 2007). Afterwards, eggs were placed back into a male's nest, which was carefully repaired.…”
Section: Methodsmentioning
confidence: 99%
“…Certain individual and territory qualities increase reproductive success, including large body size and nesting in deep water (Kraak et al 1999a). After a female spawns, she leaves the territory and the male provides all of the parental care; males continue to court females to obtain more eggs for up to three days after the first spawning (Kraak et al 1999b). During the incubation period (approximately 6 days in the population studied here), males “fan” the eggs with the pectoral fins, providing oxygen and clearing carbon dioxide (Wootton 1984) and remove rotten eggs and debris.…”
mentioning
confidence: 99%
“…Distances among nests within the pool were measured to the nearest centimeter and mapped. Following the end of the egg-collecting phase, which typically last between two to six days (Jamieson et al 1992;Kraak et al 1999a), territorial males were captured with a hand net. Sampling was done 15 days after flooding, as previous data showed that the egg-collecting phase of the male breeding cycle, which starts just after the flood, is over by then (Fitzgerald 1983).…”
Section: Study Site and Field Samplingmentioning
confidence: 99%
“…Nest location is thought to influence the predation risk affecting both the embryos and the guarding male (FitzGerald 1983;Mori 1994;Kraak et al 1999a). Based on findings of a sexual dimorphism where males had larger pectoral fins then females and considering that pectoral fins are used in parental care, several authors suggested that this trait could also be involved in mate choice (Brønseth and Folstad 1997;Bakker and Mundwiler 1999;Kü nzler and Bakker 2000).…”
mentioning
confidence: 99%